Assessment of pathogenicity of community-acquired MRSA isolates in mice-induced peritonitis - Zulkiflee, Nur Izzatie; Mat Azis, Norhidayah; Mohd Desa, Mohd Nasir; Mohtarrudin, Norhafizah; Syed Alwi, Sharifah Sakinah; Sarchio, Seri Narti Edayu (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Methicillin-Resistance Staphylococcus aureus (MRSA) is known as a major nosocomial pathogen in healthcare. However, it has now spread in the community known as community-acquired MRSA (CA-MRSA). Thus, the survival and pathogenicity of CA-MRSA isolates were assessed using in vivo peritonitis model with comparison to ATCC-MRSA. Two CA-MRSA isolates; CA-MRSA1 and CA-MRSA2 that were isolated from healthy population, were studied and compared. Methods: Mice were assigned into 4 groups and injected intraperitoneally with ATCC-MRSA, CA-MRSA1 or CA-MRSA2, respectively. Sterile Dulbecco’s Phosphate-Buffered Saline (DPBS) represents negative control. Mice were observed twice daily, 0-72 hours of post-infection. Any signs of distress were recorded for severity score and survival analyses. Mice were euthanised at 72 hours post-inoculation or by referring to the Peritonitis Severity Scoring (PSS) system. Organs of interest, peritoneal lavage and abscess were processed for bacterial counts. Tissue samples were analysed for histopathological scores. Results: All mice inoculated with MRSA showed clear signs of illness with peritonitis symptoms of p<0.001 and comparable PSS scores were recorded in all infected mice groups. Intraperitoneal injection of lethal dose of MRSA resulted in significant death of ATCC-MRSA (p<0.05) and CA-MRSA-infected mice (p<0.01), compared to the un-infected. Bacterial burden was significantly high in all samples harvested from mice challenged with CA-MRSA2 compared to ATCC-MRSA except in abscess and lung. Significant liver necrosis and spleen inflammation were observed in CA-MRSA1, and lung inflammation in ATCC-MRSA-infected mice. Conclusion: Nasal carriage CA-MRSA isolates from a healthy population has the potential to cause peritonitis with comparable severity as ATCC-MRSA.